TANGGUNG JAWAB HUKUM BADAN PENYELENGGARA KOMPETISI TERHADAP CEDERA ATLET AKIBAT KELALAIAN PENYELENGGARA PERTANDINGAN - Hapsari, Hasna Hapsari; Dea Lestari, Amanda (UIR Law Review, 2025)
Legal liability is a person's obligation to bear the consequences of an action or omission that violates applicable laws or regulations. This may include the obligation to compensate for losses, pay fines, or undergo other sanctions determined by law. This study aims to analyze the legal liability of sports competition organizers for serious injuries suffered by athletes due to negligence during the organization of the competition. In professional sports activities, athlete safety is a fundamental aspect that must be guaranteed by the organizers. However, negligence still often occurs, resulting in serious injuries. This study uses a qualitative method with a normative juridical approach by examining relevant laws and regulations, legal doctrine, and court decisions. The results show that competition organizers have legal liability based on the principle of unlawful acts (Article 1365 of the Civil Code) and the principle of responsibility based on fault (fault liability). The results show that competition organizers can be subject to civil legal liability in the form of material and immaterial compensation, while athletes can pursue civil lawsuits, mediation, or alternative resolution to obtain compensation.